2021
DOI: 10.1055/s-0041-1727557
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of ADA, IDRS, and FINDRISC in Predicting Prediabetes and Diabetes Mellitus in South Indian Population

Abstract: Introduction Diabetes risk-screening tools are validated and implemented across various countries. There is a need for improvement in these risk scores with suitable modifications so as to make them more sensitive, specific, and suitable to the local population. Objectives The aim of this study was to evaluate and compare the diagnostic accuracy and clinical utility of the Indian diabetes risk score (IDRS), the American diabetic association (ADA) risk score, and the Finnish Diabetes Risk Score in healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Consistent with this, Doddamani et al identified ADA as the preferred risk score for assessing diabetes in South India, revealing a reported diabetes prevalence of 11.9%. Notably, the ADA risk score was the sole method that showed a statistically significant difference (P= 0.05) between low-risk and high-risk patients with diabetes [12].…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with this, Doddamani et al identified ADA as the preferred risk score for assessing diabetes in South India, revealing a reported diabetes prevalence of 11.9%. Notably, the ADA risk score was the sole method that showed a statistically significant difference (P= 0.05) between low-risk and high-risk patients with diabetes [12].…”
Section: Discussionmentioning
confidence: 98%
“…Our study population showed 52.3% belonged to high-risk category and 47.7% belonged to moderate-risk category; this result was similar to the findings of Doddamani et al . [ 44 ] where 48.75% belonged to moderate IDRS risk category.…”
Section: Discussionmentioning
confidence: 99%
“…8 It is essential that proper insulin treatment is prescribed promptly to mitigate its effects and prevent further damage. 9 The increased global prevalence of diabetes mellitus has been reported in many studies and increasing prevalence day by day alarming increase risks and health complication. According to a study of 2015, >415 million adults have diabetes mellitus, and this number is estimated https://doi.org/10.29309/TPMJ/2023.30.06.7448 2 to increase to 642 million by 2040.…”
Section: Introductionmentioning
confidence: 99%